Raveron® versus placebo in the conservative treatment of benign prostatic hyperplasia (BPH) - (:unkn) unknown (Kluwer Academic Publishers, 1990)
Thirty patients with BPH were randomized into two groups to receive Raveron® and placebo for 6 weeks. The subjective and objective signs associated with BPH were evaluated before and after treatment. There was no significant difference between the effects of Raveron® and placebo. © 1990 Akadémiai Kiadó.